A Critique of Moseley's Money and Totality. (1st April 2021) - Marco, Guido De
Abstract : In his macro-monetary interpretation of Marx's theory of value, Fred Moseley claims that Marx's prices of production should be considered as the long-run equilibrium condition of capital reproduction under the assumption of given technology and given capital distribution. Moseley's methodological interpretation depends on the claim that the general rate of profit is completely predetermined in the first two volumes of Capital. I argue to the contrary that though Moseley shows the inadequacy of the Standard Interpretation, he fails to provide a convincing description of Marx's category of prices of production. The production of the new total value and total surplus-value cannot be considered as simply determined by the initial conditions of production; if we want to describe how prices of production are formed and the role they play in the social reproduction of capital, we should recognize that in social reproduction this process develops temporally through an intertwined relation between the production, circulation and distribution.